2017
DOI: 10.1371/journal.pone.0178853
|View full text |Cite
|
Sign up to set email alerts
|

Early derivation of IgM memory cells and bone marrow plasmablasts

Abstract: IgM memory cells are recognized as an important component of B cell memory in mice and humans. Our studies of B cells elicited in response to ehrlichial infection identified a population of CD11c-positive IgM memory cells, and an IgM bone marrow antibody-secreting cell population. The origin of these cells was unknown, although an early T-independent spleen CD11c- and T-bet-positive IgM plasmablast population precedes both, suggesting a linear relationship. A majority of the IgM memory cells detected after day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…In the (AID-Cre-ER T2 x Rosa26 eYFP) F 1 mice, all cells expressing AID at the time of tamoxifen administration irreversibly express eYFP ( Dogan et al, 2009 ). In our studies, few if any cells were labeled in uninfected (AID- Cre-ER T2 x Rosa26 eYFP) F 1 mice, indicating that the labeled cells were infection specific ( Papillion et al, 2017 ). Although our previous studies focused on CD11c + IgM memory cells, eYFP + B cells detected after tamoxifen administration were found to be more diverse.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…In the (AID-Cre-ER T2 x Rosa26 eYFP) F 1 mice, all cells expressing AID at the time of tamoxifen administration irreversibly express eYFP ( Dogan et al, 2009 ). In our studies, few if any cells were labeled in uninfected (AID- Cre-ER T2 x Rosa26 eYFP) F 1 mice, indicating that the labeled cells were infection specific ( Papillion et al, 2017 ). Although our previous studies focused on CD11c + IgM memory cells, eYFP + B cells detected after tamoxifen administration were found to be more diverse.…”
Section: Resultsmentioning
confidence: 56%
“…Our previous studies demonstrated that CD11c + IgM memory cells elicited during E. muris infection undergo limited somatic mutation and showed that these cells could be irreversibly labeled in (activation-induced cytidine deaminase [AID]-Cre-ER T2 x Rosa26 enhanced yellow fluorescent protein [eYFP]) F 1 mice ( Papillion et al, 2017 ). In the (AID-Cre-ER T2 x Rosa26 eYFP) F 1 mice, all cells expressing AID at the time of tamoxifen administration irreversibly express eYFP ( Dogan et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Ehrlichia muris infection model, they identified the emergence of IgM + CD11c + splenic plasmablasts 45 and memory B cells 46 that were later recognized to express T-bet. 47 These memory cells are required to generate an IgG response to secondary challenge, 46 and bone marrow IgM + antibody-secreting cells, which may arise from IgM + Tbet + precursors, protect from fatal E. muris challenge. 48 49 These cells produced virus-specific IgG2 a following in vitro stimulation and were necessary for maintaining reduced viral titers.…”
Section: Initialdescriptionsoft-bet + Bcellsinmicementioning
confidence: 99%
“…35 Considering the requirement for IFNγ or IL-21 signaling for optimal T-bet + B cell development, 73 these studies favor a germinal center-dependent origin for the subset. However, extrafollicular development of T-bet-expressing plasmablasts has been reported in E. muris-infected mice, 45,47 suggesting the potential for germinal center-independent generation under certain conditions.…”
Section: Innatesensorsignalsandth1cytokinespoise Bcellstoadoptt-betmentioning
confidence: 99%